Intraventricular Craniopharyngiomas—Overcoming Their Relative Inaccessibility: Institutional Experience With a Review of Literature - Deopujari, Chandrashekhar; Behari, Sanjay; Shroff, Krishna; Kumar, Ashutosh; Thombre, Bhushan; Karmarkar, Vikram; Mohanty, Chandan (Frontiers in Neurology, 2021)
Introduction: Craniopharyngiomas constitute 2–4% of intracranial neoplasms. Intraventricular craniopharyngiomas (IVCrs) are the rarely encountered varieties of these lesions. Objective: The objective of the study was to study the special features in clinical presentation, imaging, management, and surgical outcome of IVCrs. Materials and Methods: This retrospective analysis included the combined experience from two tertiary care institutions. Medical records of histopathologically proven cases of IVCrs from January 1994 to June 2021 were assessed, and images were analyzed based on the criteria by Migliore et al. for inclusion of solely intraventricular lesion with the third ventricular ependyma demarcating it from the suprasellar cistern. Results: Among the 25 patients included (mean age: 35.4 years), the most common presentation included headache (n = 21, 84%), vomiting and other features of raised ICP (n = 18, 72%), visual complaints (n = 12, 48%), and endocrinopathies (n = 11, 44%). Fifteen had predominantly cystic tumors, two were purely solid, and eight were of mixed consistency. Primary open microsurgical procedures were performed in 18 (72%) patients, of which four (16%) were endoscope-assisted. Seven (28%) underwent a purely endoscopic procedure. One underwent a staged surgery with endoscopic cyst fenestration and intracystic interferon (IFN)-alpha therapy, followed by microsurgical excision. Complete excision was achieved in 10 patients, near-total in nine, and partial excision in six. Four patients underwent a ventriculoperitoneal shunt (one before the definitive procedure). At a median follow-up of 36 months (range:11–147 months), five patients developed a recurrence, and one had a stable small residue. This patient and two others with small cystic recurrences were observed. One patient was managed with radiotherapy alone. Another underwent re-surgery after a trial of radiotherapy, and the last patient developed a local recurrence, which was managed with radiotherapy; he then later developed an intraparenchymal recurrence, which was operated. Conclusion: Purely IVCrs present with raised intracranial pressure, and visual disturbances are less common. Their deep-seated location and limited surgical field-of-view makes minimally invasive endoscopic-assisted surgery most suitable for their excision. The thin-walled cystic lesions may be occasionally adherent to the ependymal wall in close vicinity to the thalamus–hypothalamus complex, making complete excision difficult. Their responsiveness to radiotherapy, often leads to a gratifying long-term outcome.